Amoxicillin-docosahexaenoic acid encapsulated chitosan-alginate nanoparticles as a delivery system with enhanced biocidal activities against Helicobacter pylori and improved ulcer healing - Khoshnood, Saeed; Negahdari, Babak; Kaviar, Vahab Hassan; Sadeghifard, Nourkhoda; Abdullah, Mohd Azmuddin; El-Shazly, Mohamed; Haddadi, Mohammad Hossein (Frontiers in Microbiology, 2023)
Encapsulation of amoxicillin (AMX) for drug delivery against Helicobacter pylori (H. pylori) infection and aspirin-induced ulcers in rats' stomachs was performed using docosahexaenoic acid (DHA)-loaded chitosan/alginate (CA) nanoparticles (NPs) developed by ionotropic gelation method. The physicochemical analyses of the composite NPs were performed by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), zeta potential, X-ray diffraction (XRD), and atomic force microscopy (AFM). The encapsulation efficiency of AMX was increased to 76% by incorporating DHA, which resulted in a reduction in the particle size. The formed CA-DHA-AMX NPs effectively adhered to the bacteria and rat gastric mucosa. Their antibacterial properties were more potent than those of the single AMX and CA-DHA NPs as demonstrated by the in vivo assay. The composite NPs attained higher mucoadhesive potential during food intake than during fasting (p = 0.029). At 10 and 20 mg/kg AMX, the CA-AMX-DHA showed more potent activities against H. pylori than the CA-AMX, CA-DHA, and single AMX. The in vivo study showed that the effective dose of AMX was lower when DHA was included, indicating better drug delivery and stability of the encapsulated AMX. Both mucosal thickening and ulcer index were significantly higher in the groups receiving CA-DHA-AMX than in the groups receiving CA-AMX and single AMX. The synergistic effects of AMX and the CA-DHA formulation increased the biocidal activities against H. pylori infection and improved ulcer healing properties.